2020
DOI: 10.17645/pag.v8i1.2560
|View full text |Cite
|
Sign up to set email alerts
|

Populism and Political Knowledge: The United States in Comparative Perspective

Abstract: This article addresses the link between political knowledge and populist attitudes in the United States (US) in comparative perspective. At the beginning of the new decade, populism in the US is associated with support for the Republican party and Donald Trump in particular, and that is how I address it here. Using secondary data from a number of related studies, we find that, overall, support for Trump is not only negatively related to political knowledge, but also to other factors that make his supporters un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
3
0
2
Order By: Relevance
“…We know, for example, that the effect of populist messages on several types of attitudes are moderated by whether or not someone supports a populist party (Rooduijn et al, 2017). Fourth, as populism has often been linked to education and political sophistication, that is, people with lower levels of education and sophistication being more likely to be populist (Elchardus & Spruyt, 2016; Milner, 2020; Spruyt et al, 2016), we expect that educational attainment and political sophistication are moderators too.…”
Section: Emotional Populist Rhetoricmentioning
confidence: 99%
“…We know, for example, that the effect of populist messages on several types of attitudes are moderated by whether or not someone supports a populist party (Rooduijn et al, 2017). Fourth, as populism has often been linked to education and political sophistication, that is, people with lower levels of education and sophistication being more likely to be populist (Elchardus & Spruyt, 2016; Milner, 2020; Spruyt et al, 2016), we expect that educational attainment and political sophistication are moderators too.…”
Section: Emotional Populist Rhetoricmentioning
confidence: 99%
“…Sin embargo, el populismo no tiene un efecto significativo sobre la APC. Este dato podría explicarse por el hecho de que los partidarios de formaciones políticas populistas no suelen darse cuenta de que están mal informados (Milner, 2020). También se ha detectado en la presente investigación, un efecto poco potente del nivel de populismo de los participantes sobre su capacidad de detección de noticias falsas, siendo, aun así, más proclives a su detección las personas de ideología no populista.…”
Section: Discusión Y Conclusionesunclassified
“…El populismo, por tanto, comparte rasgos de la denominada posverdad, y en este sentido, hay autores que subrayan la relación del populismo con la desinformación (Milner, 2020) y el incremento del infoentretenimento (Berrocal Gonzalo, 2014). La posverdad se define como "relating to or denoting circumstances in which objective facts are less influential in shaping public opinion compared to appeals to emotion and personal beliefs" (Flood, 2016).…”
unclassified
“…It has been shown that voters with low political knowledge had significantly more sympathy for Trump, relied more heavily on their emotions, and were thus more trustful about statements made by Trump (Fording/Schram 2017). Trump supporters were also less aware of being misinformed and generally knew less about policies and politics (Milner 2020).…”
Section: Right-wing Populist Support and Political Knowledgementioning
confidence: 99%